2015
DOI: 10.1016/j.jcot.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis of Soleus muscle presenting as isolated calf pain

Abstract: Magnetic resonance imaging a b s t r a c tCNS is the most common site of involvement by cysticercosis. Symptomatic involvement of isolated skeletal muscle by solitary cysticercosis cyst is extremely rare. We report a rare and unusual case of cysticercosis presenting as acute calf pain, which is a diagnostic challenge. But the diagnosis was reached by sero-radiological examination and patient was managed conservatively by medical means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Only a few case reports of isolated muscular cysticercosis have been reported in the English literature. [8][9][10][11][12][13] Probably it is the first case report of isolated brachialis muscle involvement by cysticercosis. Muscular cysticercosis often goes unnoticed because it remains asymptomatic in most individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case reports of isolated muscular cysticercosis have been reported in the English literature. [8][9][10][11][12][13] Probably it is the first case report of isolated brachialis muscle involvement by cysticercosis. Muscular cysticercosis often goes unnoticed because it remains asymptomatic in most individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Cysticercosis is a parasitic infection that is caused by Taenia solium and is common in developing countries, where persons are infected by eating improperly cooked pork (45,46). The central nervous system is the most common site of symptomatic disease; when cysticercosis affects muscle, there is typically concomitant neural involvement (45,46). Muscle involvement by cysticercosis can be asymptomatic or manifest as myalgia, a solitary mass, or, most commonly, multiple intramuscular cysts (46) (Fig 14).…”
Section: Cysticercosismentioning
confidence: 99%
“…The central nervous system is the most common site of symptomatic disease; when cysticercosis affects muscle, there is typically concomitant neural involvement (45,46). Muscle involvement by cysticercosis can be asymptomatic or manifest as myalgia, a solitary mass, or, most commonly, multiple intramuscular cysts (46) (Fig 14). The appearance of intramuscular lesions varies as the disease progresses through its vesicular, colloid, granular-nodular, and calcific stages (47).…”
Section: Cysticercosismentioning
confidence: 99%
See 1 more Smart Citation
“…Lesions were confirmed by cytology and histopathology. Pallav et al (12) reported an unusual case of cysticercosis in the right soleus muscle that presented as acute calf pain and difficulty in walking. Enzyme-linked immunosorbent assay (ELISA) for IgG antibodies against Taenia solium was positive, which confirmed the diagnosis.…”
mentioning
confidence: 99%